2013
DOI: 10.3892/ol.2013.1280
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of CD155 mRNA expression in soft tissue sarcomas

Abstract: CD155 was initially identified as a receptor for poliovirus. Several studies have demonstrated that CD155 overexpression in cancer cells is significant in their migration, invasion, proliferation and metastasis. The objective of the present study was to investigate the correlation between CD155 expression and the clinical aggressiveness of soft tissue tumors. The CD155 expression levels in 43 surgically-resected soft tissue tumors were evaluated using the quantitative real-time polymerase chain reaction (PCR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…The 347 CD155-associated hypo-immune response in the tumor microenvironment of 348 LUAD could lead to immune invasion and promote tumor growth. In addition, 349 CD155 high patients showed poorer survival than CD155 low patients, which was 350 in accordance with a previous report (Atsumi et al, 2013). Interestingly, we 351 found that CD155 expression did not affect cancer cell proliferation in vitro or 352 tumor growth in vivo.…”
Section: Cd155-independent Tumor Growth In Luadcs 213supporting
confidence: 85%
“…The 347 CD155-associated hypo-immune response in the tumor microenvironment of 348 LUAD could lead to immune invasion and promote tumor growth. In addition, 349 CD155 high patients showed poorer survival than CD155 low patients, which was 350 in accordance with a previous report (Atsumi et al, 2013). Interestingly, we 351 found that CD155 expression did not affect cancer cell proliferation in vitro or 352 tumor growth in vivo.…”
Section: Cd155-independent Tumor Growth In Luadcs 213supporting
confidence: 85%
“…Moreover, while previous studies have demonstrated expression and clinical relevance of CD112 and CD155 mostly from a sarcoma subset-oriented perspective (24,63,65), here we simultaneously assessed the expression of CD112 and CD155 in a diverse group of primary human sarcomas. The restricted expression of these molecules in healthy tissues, combined with the expression on all sarcoma explants provides valuable information regarding potential new targets for the development of targeted immunotherapies for sarcoma (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a large number of research studies have stipulated that PVR overexpression in tumors is a direct marker of tumor progression and correlates with a worse survival prognosis, suggesting that this protein has a role in tumor pathology. 20,56,62 Accordingly, researchers have proposed that increased PVR expression promotes tumor cell invasion, migration, proliferation, and angiogenesis through a similar mechanism as used to exert its regular effects on these processes in healthy cells. [7][8][9][10] For example, due to the involvement of PVR in cellular motility and leading-edge formation, PVR overexpression enhances tumor cell motility and PVR knockdown suppresses tumor cell invasiveness and decreases their migration in vitro.…”
Section: Rationale For the Development Of Strategies Targeting Pvr Inmentioning
confidence: 99%